Identifying church members' programming usage, satisfaction, and needs - Pillainayagam, Jeanna; Thiruchelvam, Etisha; Patel, Vidhi; Frank, Fayth; Lai, Aiping (Prepared by the McMaster Research Shop for the Church of St. John the Evangelist, 2024)
The Church of Saint John the Evangelist (The Rock on Locke) serves the Kirkendall and Durand neighbourhoods, offering various programs to its approximately 200 congregation members. To better understand how these programs are meeting the needs of its community, the Research Shop conducted a needs assessment using a comprehensive survey and key informant interviews. This report summarizes our findings, providing insights into the congregation’s program awareness and usage, satisfaction levels, and potential service gaps.
Keywords: Hamilton, community-engaged research, program evaluation, faith community